Definition. If $f: X \to Y$ is a smooth map and $\omega$ is a $p$-form on $Y$, define a $p$-form $f^*\omega$ on $X$ as follows: $$f^*\omega(x) = (df_x)^*\omega[f(x)].$$

According to Daniel Robert-Nicoud's nice answer to $f: X \to Y$ is a smooth map and $\omega$ is a $p$-form on $Y$, what is $\omega[f(x)]$?, locally, differential form can be written as $$\omega_\alpha(y) = \alpha(y)dx^{i_1}\wedge\ldots\wedge dx^{i_p}$$ with $\alpha$ a smooth function. Then $$f^*\omega_\alpha(x) = (df_x)^*[(\alpha\circ f)(x)dx^{i_1}\wedge\ldots\wedge dx^{i_p}].$$

Hence, if $$\omega_\alpha(y) = \alpha(y)dx^{i_1}\wedge\ldots\wedge dx^{i_p},$$ $$\theta_\beta(y) = \beta(y)dx^{j_1}\wedge\ldots\wedge dx^{j_q},$$

Do I get $\omega \wedge \theta$ such that $$\omega_\alpha \wedge \theta_\beta(y)= \gamma(y)dx^{k_1}\wedge\ldots\wedge dx^{k_{p+q}}?$$ If so, how can I prove it?

And can I write $\gamma$ in terms of $\alpha$ and $\beta$?

Thank you~~~


I suppose generally a $p$-form is a sum of such terms, but if we can understand how one such element pulls-back then linearity extends to $\sum_{i_1, \dots , i_p}\alpha_{i_1,\dots , i_p} dy^{i_1} \wedge \cdots \wedge dy^{i_p}$. That said, to calculate $\gamma$ you just have to sort out the sign needed to arrange the indices on the wedge of $\omega_{\alpha} \wedge \theta_{\beta}$. I prefer the notation, assuming $I \cap J = \emptyset$, $$ (\alpha dy^I) \wedge (\beta dy^J) = \alpha \beta dy^I\wedge dy^J = \alpha \beta (-1)^{\sigma(I,J)}dy^K $$ here $\alpha\beta$ merely indicated the product of the scalar-valued functions $\alpha$ and $\beta$ and I have suppressed the $y$-dependence as it has little to do with the question. Here $\sigma(I,J)$ is the number of transpositions needed to rearrange $(I|J)$ into $K$.

Of course, you could just leave the $I$ and $J$ unchanged in which case the $\gamma = \alpha \beta$. I rearranged them because in some of what you are interested in reading there will be a supposition that the indices are arranged in increasing order so if $I = (1,2,5)$ and $J = (3,6)$ then you'll want $(1,2,5)(3,6) \rightarrow K = (1,2,3,5,6)$ which requires flipping $3$ and $5$ hence $\sigma(I,J) = 1$. Ok, usually we use "sgn" of a permutation to get this sign so my notation is a bit nonstandard.

  • $\begingroup$ Thank you so much James, you are really leading me through!!!!! $\endgroup$ – WishingFish Jul 31 '13 at 3:58
  • $\begingroup$ I know $T \wedge S = (-1)^{|T||S|} S \wedge T$. But we are not commuting $dy^I, dy^J$ here, why still? $\endgroup$ – WishingFish Jul 31 '13 at 4:01
  • $\begingroup$ hmm, you really know what I am thinking! I see you answered before I post the comment above asking about it.... :) $\endgroup$ – WishingFish Jul 31 '13 at 4:02
  • $\begingroup$ So $\sigma(I,J)$ is the sign function bookkeeping how many commute actually happened to combine the wedge sorted, rather than commute the whole $dy^I$ and $dy^J$ - now it makes sense. thanks :) $\endgroup$ – WishingFish Jul 31 '13 at 4:04
  • $\begingroup$ @WishingFish I probably would do better to write $\sigma(I,J)=K$ and $dy^I \wedge dy^J= sgn(\sigma)dy^K$, I think that notation is a standard notation. $\endgroup$ – James S. Cook Jul 31 '13 at 4:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.